1994
DOI: 10.2527/1994.7261540x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects among porcine somatotropin, the beta-adrenergic agonist salbutamol, and dietary lysine on growth performance and nitrogen balance of finishing swine2

Abstract: An experiment was conducted to evaluate the interactive effects among porcine somatotropin (pST), salbutamol, and dietary lysine on growth performance, nitrogen balance, and carcass characteristics of finishing barrows (n = 32; 62.8 kg initially). Two replicate 32-d studies were set up in a split-plot design to evaluate singular and combined use of pST (0 or 4 mg/d) and salbutamol (0 or 2.75 ppm of the diet) as whole-plot treatments and diets containing .8, 1.2, 1.6, or 2.0% lysine as subplot treatments. Dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…Therefore, that hypothesis suggests a reduction in weight of noncarcass components in ZH ewe lambs as a consequence of an increase in carcass muscle mass. However, Montgomery et al (2009) raised this hypotli-csis based on results from pigs (Hansen et al, 1994) and mice (Sharma et al, 1997), where liver and kidney weight decreased significantly by oral administration of clembuterol and salbutamol. However, no effect of ZH was observed on visceral organs in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, that hypothesis suggests a reduction in weight of noncarcass components in ZH ewe lambs as a consequence of an increase in carcass muscle mass. However, Montgomery et al (2009) raised this hypotli-csis based on results from pigs (Hansen et al, 1994) and mice (Sharma et al, 1997), where liver and kidney weight decreased significantly by oral administration of clembuterol and salbutamol. However, no effect of ZH was observed on visceral organs in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Although the effects of lysine on protein deposition were relatively small, which may have hindered curve fitting, there was sufficient evidence for these authors to conclude that the lysine requirement for pST-treated pigs was approximately 10 to 12 g/kg. Hansen et al (1994) conducted a nitrogen balance study in pigs over the live weight range of 63 to 99 kg and concluded that the lysine requirement of pigs injected with 4 mg pST/d was 12 g/kg. A difficulty with interpretation of this study was that the levels of dietary lysine were in 4 g/kg increments between 8 and 20 g/kg, making it hard to interpolate between 8 and 12 g lysine/kg.…”
Section: Resultsmentioning
confidence: 99%
“…leitoas com alta capacidade de deposição de carne magra na carcaça, dos 50 aos 80 kg. Por outro lado, considerando os dados de consumo de lisina diário, os resultados obtidos neste estudo estão coerentes com os obtidos por diversos autores (CROMWELL et al, 1993;OWEN et al, 1994;HANSEN et al, 1994;SUSENBETH et al, 1994;e HAHN et al, 1995), que variaram de 22 a 25,5 g/dia, para suínos em terminação.…”
Section: Resultsunclassified